2000
DOI: 10.1302/0301-620x.82b8.0821196
|View full text |Cite
|
Sign up to set email alerts
|

Tibiofemoral movement 2: the loaded and unloaded living knee studied by MRI

Abstract: In 13 unloaded living knees we confirmed the findings previously obtained in the unloaded cadaver knee during flexion and external rotation/internal rotation using MRI. In seven loaded living knees with the subjects squatting, the relative tibiofemoral movements were similar to those in the unloaded knee except that the medial femoral condyle tended to move about 4 mm forwards with flexion. Four of the seven loaded knees were studied during flexion in external and internal rotation. As predicted, flexion (squa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
146
2
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(168 citation statements)
references
References 4 publications
9
146
2
3
Order By: Relevance
“…Group A consisted of ten female and seven male, 13 left knee, average age of 69.3 years old (45-81). Their average knee score was 169.3 (120-198) representing 11 category A patients, 4 category B and 2 category C. The average follow up was 10.7 months (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Group B consisted of 13 female and 5 male, 7 left knee, …”
Section: Clinical Resultsmentioning
confidence: 99%
“…Group A consisted of ten female and seven male, 13 left knee, average age of 69.3 years old (45-81). Their average knee score was 169.3 (120-198) representing 11 category A patients, 4 category B and 2 category C. The average follow up was 10.7 months (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Group B consisted of 13 female and 5 male, 7 left knee, …”
Section: Clinical Resultsmentioning
confidence: 99%
“…Static MRI studies of normal knees have shown that the lateral condyle translated more than the medial condyle in deep knee flexion [19,22]. The ACL/PCL knees showed greater posterior translation of the lateral condyle than PCL knees during the kneeling and lunge activities.…”
Section: Discussionmentioning
confidence: 99%
“…Maximum flexion in kneeling was 135°±14°for unicondylar knees and 123°±14°for bi-unicondylar knees (p=0. 22). For 0°-30°flexion during the stair activity, the medial condyle translated posterior 3.5±2.5 mm in unicondylar knees and 4.7±1.9 mm in bi-unicondylar knees (p>0.05).…”
mentioning
confidence: 86%